Evaluation esthetic and functional outcomes after rhinoplasty - Hawrami, Falah Abdulla Hussein; Amin, Zanyar M.; Mahmood, Muhammad; Hama, Rebwar A. (Journal of Contemporary Medical Sciences, 2020)
Objective: The aim of this study was to determine patient satisfaction in regard to nose appearance and function with the use of a validated questionnaire, before and after rhinoplasty surgery. Methods: A prospective study was conducted of all adult patients that underwent open rhinoplasty including other nasal procedures like septoplasty or turbinoplasty between September 2018 and August 2019 in both public and private hospital (Sulaimani Surgical Teaching Hospital and Faruk Medical City).The Rhinoplasty Outcome Evaluation (ROE) questionnaire was used to study the patients' view. Results: 100 patients participated in this study by completing the questionnaires and the follow-up period. The main reasons for rhinoplasty in our patients were: aesthetic 54% (n=54), functional 2 %( n=2), and a combination of both in 44% (n=44) patients The mean ROE score of all patients pre operation was 51.8 (males: 49.04, females 54.74.) and the mean score post operation was 75.22(males 75.64, females 74.81) at six months with no statistically significant gender differences p value=0.79 However, both genders showed a statistically significant improvement between the preoperative and postoperative scores (mean difference = 23.42, P<0.017).In the pre-operative stage, patients recorded worse score for anxious and insecure (p < 0.05). There were no difference for gender, age, cause or literacy level in the mean post-operative scores (p > 0.05). Conclusions: We found that patients who consider themselves anxious before surgery were less satisfied with the result of the procedure. Additionally Rhinoplasty surgery significantly improved patient quality of life regarding nose shape and function.